Self-Harm Among School-Going Adolescent Survivors of Sexual Violence Victimisation: A Cross-Sectional Study - Quarshie, Emmanuel Nii-Boye (Frontiers in Sociology, 2021)
Background: A growing body of evidence from high-income contexts suggests a strong association between sexual violence victimisation and self-harm and eventual suicide. However, both sexual violence and self-harm among adolescents are still less researched in sub-Saharan African countries, including Ghana. Objectives: To estimate the 12-month prevalence of self-harm, and to describe the associated factors and reported reasons for self-harm among school-going adolescent survivors of sexual violence victimisation during the previous 12 months in urban Ghana. Methods: Analytic data came from a regional-based representative cross-sectional survey including in-school youth (N = 1,723) conducted in 2017 within the Greater Accra Region of Ghana. Of these, 297 (17.2%) self-reported sexual violence victimisation in the previous 12 months; this proportion of the participants (n = 297) was the focus of the current study. Items measuring sexual violence victimisation, self-harm, and correlates were adopted from the 2012 Ghana WHO–Global School-based Student Health Survey and the Child and Adolescent Self-harm in Europe Study. Data analysis involved multivariable logistic regression models. Results: The estimate of self-harm ideation during the previous 12 months was 45.8% (95% CI: 40–52), whereas the estimate of self-harm behaviour was 38.7% (95% CI: 33–44). About two in five of the participants who reported self-harm wanted to die by their last episode of the behaviour. While bullying victimisation was associated with increased odds of self-harm ideation (aOR = 1.97, 95% CI 1.17, 3.31, p = 0.010) and behaviour (aOR = 2.76, 95% CI 1.59, 4.80, p < 0.001), weekly alcohol use (aOR = 2.56, 95% CI 1.32, 4.93, p = 0.005), conflict with parents (aOR = 2.30, 95% CI 1.28, 4.12, p = 0.005), and physical abuse victimisation (aOR = 1.80, 95% CI 1.03, 3.15, p = 0.037) showed strong associations with increased odds of self-harm behaviour in the past 12 months. Conclusions: The evidence underscores the need for both universal and targeted multi-level intervention and prevention programmes to mitigate the offence of sexual violence and reduce the chances of self-harm among adolescent survivors of sexual violence in urban Ghana.